2018
DOI: 10.26905/jbm.v5i1.2321
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Variabel Makroekonomi Dan Harga Saham Asing Terhadap Indeks Harga Saham Gabungan

Abstract: This study aimed to analyze the effect of macroeconomic variables and foreign stock price on Jakarta Composite Index (JCI) in Indonesia Stock Exchange covering the data period from January 2008 to December 2015. The methodology applied initially used the standard time series techniques, Vector Autoregression (VAR). The result showed that JCI are influenced with the selected macroeconomic and foreign stock price. Increasing in industrial production index and inflation will increase JCI, but exchange rate (Rp/US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 1 publication
2
8
2
3
Order By: Relevance
“…= 0962 > 0.05, it can be deduced to accept H0 and reject Ha3 which means United States Dollar variable is insignificant effect on the CSPI. The results of this study contradict the research conducted by Bella & Ari (2018), R. Safiroh Febrina, et al (2018), Fatus All Anati, et al (2018), Winda Wulandaeri, et al (2019, Sulaeman & Erwin (2017) who showed that the United States Dollar was negatively and significantly effect in the CSPI. As well as research done by Murtini & Septivanie (2016), Armelia & Yudhinanto (2018), H. Medyawati & M. Yunanto (2016) which shows that the United States Dollar has a positive and significant effect on the CSPI.…”
Section: Influence Of United States Dollar On the Composite Stock Pricontrasting
confidence: 99%
See 3 more Smart Citations
“…= 0962 > 0.05, it can be deduced to accept H0 and reject Ha3 which means United States Dollar variable is insignificant effect on the CSPI. The results of this study contradict the research conducted by Bella & Ari (2018), R. Safiroh Febrina, et al (2018), Fatus All Anati, et al (2018), Winda Wulandaeri, et al (2019, Sulaeman & Erwin (2017) who showed that the United States Dollar was negatively and significantly effect in the CSPI. As well as research done by Murtini & Septivanie (2016), Armelia & Yudhinanto (2018), H. Medyawati & M. Yunanto (2016) which shows that the United States Dollar has a positive and significant effect on the CSPI.…”
Section: Influence Of United States Dollar On the Composite Stock Pricontrasting
confidence: 99%
“…This research is in line with the research conducted by Sulaeman & Erwin (2017), R. Safiroh Febrina, et al (2018), Fatus All Anati, et al (2018), Armelia & Yudhinanto (2018) which shows that the Dow Jones Industrial Average has a positive and significant impact on the CSPI.…”
Section: Influence Of the Dow Jones Industrial Average On The Composisupporting
confidence: 90%
See 2 more Smart Citations
“…Dalam hal investasi saham saat Covid-19, responden cenderung yakin dengan pemerintah dan track record Indonesia dalam mengatasi berbagai permasalahan ekonomi sehingga responden cenderung tidak memperdulikan dan menghiraukan kondisi perekonomian Indonesia saat ini. Hal ini berbanding terbalik dengan penelitian Febrina (2018) yang mengatakan respon investor dipengaruhi oleh makroekonomi sebagai faktor dominan di Bursa Efek Indonesia.…”
Section: Pembahasanunclassified